2019
DOI: 10.1007/s13197-018-03557-w
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and antioxidant potential of some wild edible mushrooms of Nagaland, India

Abstract: Mushrooms are known to mankind since early human civilization and are gaining importance because of their nutritional and medicinal properties. Till date 37 wild edible mushrooms are reported from Nagaland. In this study, nutritional analysis including total phenolics, flavonoids and antioxidant activity was done for ten popular WEM species. Total protein content was found to be high which ranged from 62.27 g/100 g (Lentinus sajor-caju) to 18.77 g/100 g (Lentinus squarrosulus var. squarrosulus); total carbohyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 25 publications
(21 reference statements)
3
10
1
Order By: Relevance
“…So far, there has been no report on the nutritional content of L. leptomerus ; therefore, in this study, we report for the first time that L. leptomerus J201 contains an adequate value of 20.8% protein per dw. A previous study reported that another species of Lactifluus, L. piperitus , a species of the subgenus Lactifluus from Nagaland, contained 19.33% protein, which is almost similar to our study on the same subgenus [ 35 ].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…So far, there has been no report on the nutritional content of L. leptomerus ; therefore, in this study, we report for the first time that L. leptomerus J201 contains an adequate value of 20.8% protein per dw. A previous study reported that another species of Lactifluus, L. piperitus , a species of the subgenus Lactifluus from Nagaland, contained 19.33% protein, which is almost similar to our study on the same subgenus [ 35 ].…”
Section: Resultssupporting
confidence: 89%
“…The protein content of the species investigated was found to be 37.6%, 20.8% and 16.4%, corresponding to M. gigantea J124, L. leptomerus J201 and R. thindii J470, respectively. For M. gigantea J124, the protein content is 37.6%, which is slightly higher than previously studied [ 35 ], while the protein content is in correlation with another previously reported study for the same mushroom [ 13 ]. A previous report on the protein content of different Ramaria species ranged from 10.81 to 21.65%, which correlated with our finding of 16.4% for R. thindii J47 [ 17 ].…”
Section: Resultssupporting
confidence: 87%
“…For nutrient analysis of other species of Termitomyces, Ugbogu et al (2018) showed that the fruit body of Termitomyces robustus had 18.44 ± 0.09% crude protein, 62.63 ± 0.53% carbohydrates, 2.88 ± 0.04% crude fat and 3.10 ± 0.15% acid ascorbic. Total fruit body protein and carbohydrate of Termitomyces heimii were 60.53 ± 0.01% and 22.74 ± 0.01% of dry weight respectively, while moisture was 81.1 ± 0.02%, and no data for fat content was showed (Ao & Deb, 2019). These results showed that the nutrients of species of Termitomyces were so different.…”
Section: Chemical Components Of T Clypeatus's Mycelia Cultured In the Stirred-tank Bioreactormentioning
confidence: 86%
“…Yang et al [ 131 ] extracted and explored the antioxidant properties of a novel polysaccharide fraction from C. cornucopioides . Ao et al [ 132 ] described antioxidant activity (IC50 47.5 μg/mL) of Lentinus tigrinus from Nagaland, India. Phenolic extract of Agaricus brasiliensis exhibited antioxidant activity, assessed by DPPH (50.64 μmolTE/g) and ABTS (128.60 μmolTE/g) assays [ 133 ].…”
Section: Microorganisms As a Source Of Antioxidant Compoundsmentioning
confidence: 99%